NILAI PERUSAHAAN: DAPATKAH DIPENGARUHI OLEH KEBIJAKAN DEVIDEN, CSR, STRUKTUR MODAL DAN PROFITABILITAS? - Kodriyah Kodriyah; Denny Kurnia; Santi Octaviani (Accounthink, 2021)
This study has the objective to test the factors that can have an impact on the increase or decrease in the value of the company. Company Subsector Coal Mining which are listed in Indonesia stock Exchange as the population in this study with the research period for 4 years i.e. from the year 2016 up to 2019. Based on the criteria that have been set obtained a sample of 10 companies with a total data of as many as 40. Multiple Regression analysis into the data analysis technique used in this study and data were processed using the SPSS Statistic 20. The results of the study showed that dividend policy does not affect the increase or decrease in the value of the company, Corporate Social Responsibility can affect the value of the company is positive and significant, capital Structure has no influence on the increase or decrease in the value of the company while profitability may affect the value of the company in a positive and significant. With the results of this study hopefully can contribute to the investors to take the right investment decisions based on the assessment of investors to the value of the company.